Molecular diversity and pathogenic variability in Colletotrichum capsici of chilli (Capsicum annuum) in Haryana - DEYOL, ALKA; TAUNK, JYOTI; KHIRBAT, S K; YADAV, R C (The Indian Journal of Agricultural Sciences, 2015)
The fruit rot of chilli (Capsicum annuum L.), caused by Colletotrichum capsici, is the most serious disease of chilli in India. Fourteen isolates of C. capsici collected from different locations in Haryana state were investigated for molecular variations along with their virulence pattern. Different levels of virulence were expressed dividing isolates into four groups. Out of 33 primers, 22 exhibited DNA polymorphism producing a total of 108 bands with an average of 4.90 bands per primer. At an arbitrary cut-off at 45% similarity level of dendrogram, the isolates were clustered into two main clusters. The grouping of the isolates based on RAPDs was in general neither in agreement with their pathogenicity on different host cultivars nor with the geographical location of the isolate. The information may be helpful in improving chilli fruit rot resistance and varietal deployment strategies essential for effective disease management.